DEVELOPING A TOOL TO ASSESS HIGH ORDER THINKING SKILL ABOUT THE IMMUNE SYSTEM IN HIGH SCHOOL - Viola Fitri Maharani; Yosi Laila Rahmi; Helendra Helendra; Rahmawati D; Jailani Jailani (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Implementation of the 2013 curriculum is able to create students who have high-level thinking skills. One way to overcome is to develop an instrument for higher-order thinking skills. This study aims to produce an instrument for assessing higher order thinking skills about the immune system for class XI SMA/ MA that is logically valid, empirical, practical, reliable, moderate difficulty level, discriminatory power and good option quality. This study uses a 4-D models development model. The subjects of this study were two biology lecturers at UNP and one teacher at SMAN 2 Solok City, as well as 32 class XI students. Data collection instruments is questionnaire. This data was analyzed using the ANATES 4.09 application. Based on the results of data analysis, the average value of logical validity was 86.2% with a valid category, an average practicality value of 91.66% with a very practical category, moderate difficulty level, good discriminating power, 52% option quality and reliability with percentage 0.83. Based on the results of the study, it can be concluded that the instrument for assessing high-level thinking skills about immune system material is logically and empirically valid, practical, reliable, moderate difficulty, discriminatory power and good quality of options.